2008
DOI: 10.1002/pon.1492
|View full text |Cite
|
Sign up to set email alerts
|

The influence of acculturation and breast cancer‐specific distress on perceived barriers to genetic testing for breast cancer among women of African descent

Abstract: Objective-Rising health disparities are increasingly evident in relation to use of genetic services (including genetic counseling and testing) for breast cancer risk, with women of African descent less likely to use genetic services compared with Whites. Meanwhile, little is known regarding potential within-group acculturation and psychological differences underlying perceived barriers to genetic testing among women of African descent.Methods-Hypothesized contributions of acculturation factors and breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 68 publications
1
32
0
2
Order By: Relevance
“…Ten studies, all conducted in the US, examined breast cancer, either exclusively 24,33,34 or along with other types of cancers. 32,35 Six were quantitative 23,24,32,34,36,37 and four used qualitative methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies, all conducted in the US, examined breast cancer, either exclusively 24,33,34 or along with other types of cancers. 32,35 Six were quantitative 23,24,32,34,36,37 and four used qualitative methods.…”
Section: Resultsmentioning
confidence: 99%
“…32,35 Six were quantitative 23,24,32,34,36,37 and four used qualitative methods. 33,35,38,39 Paper foci included breast cancer prevention 34 and detection, including barriers to genetic testing 24 and barriers to mammography screening. 23,32,37,3833,35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, with regard to educational level, women with higher levels of education were more likely to continue genetic counseling [14,16], even if, an American study reported that women with high school qualifications were less interested in counseling [17].…”
Section: Introductionmentioning
confidence: 99%
“…While, other studies instead have reported that psychological distress (particularly cancer-specific distress, that is anxiety and depression associated with worrying about cancer) was significantly associated with the refusal or the withdrawal from genetic counseling, whether levels were high or low. A moderate level of distress (general distress and cancer-specific distress) was found to facilitate the decision to undergo genetic counseling [16,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%